2006
DOI: 10.1111/j.1360-0443.2006.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Does subtle screening for substance abuse work? A review of the Substance Abuse Subtle Screening Inventory (SASSI)

Abstract: No empirical evidence was found for the SASSI's claimed unique advantage in detecting substance use disorders through its indirect (subtle) scales to circumvent respondent denial or dishonesty. Recommendations for screening and for future research with the SASSI are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Not all investigators who examined the SASSI reported a positive conclusion. Feldstein and Miller's (2007) literature review led them to conclude that “no independent peer‐reviewed substantiation was found for the SASSI's claimed unique advantage in detecting SUDs through its indirect (subtle) scales, by circumventing respondent denial or dishonesty” (p. 49). Lazowski and Miller (2007) deflected this criticism by noting that only three of the 10 criterion‐related validity studies cited by Feldstein and Miller were performed using the most recent version of the SASSI‐3.…”
mentioning
confidence: 99%
“…Not all investigators who examined the SASSI reported a positive conclusion. Feldstein and Miller's (2007) literature review led them to conclude that “no independent peer‐reviewed substantiation was found for the SASSI's claimed unique advantage in detecting SUDs through its indirect (subtle) scales, by circumventing respondent denial or dishonesty” (p. 49). Lazowski and Miller (2007) deflected this criticism by noting that only three of the 10 criterion‐related validity studies cited by Feldstein and Miller were performed using the most recent version of the SASSI‐3.…”
mentioning
confidence: 99%
“…Another 21.89% (12 male adolescents, 18 female adolescents) qualified for further assessment for a probable substance-related disorder using the SASSI-A2 validity check. A good study of the SASSI-A2 should provide criterion validity for each scale so that the information can be compared with other research on SASSI-A2 (Feldstein & Miller, 2007). In our study, a closer look at the different criteria that screen in our sample for a possible substance abuse disorder may provide a better understanding of how the SASSI-A2 screens ethnic minorities for such a disorder.…”
Section: Main Analysesmentioning
confidence: 89%
“…Substance Abuse Subtle Screening Inventory‐3 (SASSI‐3) . The SASSI‐3 is a screening instrument designed to detect the presence of substance‐use disorders regardless of the truthfulness or motivation of the individuals completing the instrument (Feldstein & Miller, 2007). The SASSI‐3 form is double‐sided, with the front side containing 67 true/false questions that are unrelated to alcohol or drug use.…”
Section: Methodsmentioning
confidence: 99%
“…The SASSI‐3 contains nine decision rules that are based on either individual or combined scales' values. When respondents exceed the cutoff for any of the nine decision rules, they are identified as having a high probability of having a substance‐dependence disorder; however, if all criteria are below the specified cutoffs, these respondents are considered to have a low probability of having a substance‐dependence disorder (Feldstein & Miller, 2007). In addition to this dichotomous approach to determining the likelihood of substance dependence, raw scores for each scale can be converted to T‐scores with associated percentile scores.…”
Section: Methodsmentioning
confidence: 99%